A thermo-mechanical model for hot cracking susceptibility in electron beam powder bed fusion of Ni-base superalloys - Wahlmann, Benjamin; Markl, Matthias; Körner, Carolin (Materials & Design, 2024)
Hot cracking is a major challenge in the additive manufacturing of Ni-base superalloys. Most cracking indicators only consider the alloy composition and its effects on solidification behavior, strength, and ductility. We propose a new model that extends these classical cracking indicators by additionally incorporating the transient thermo-mechanical state during melting and solidification. The model is derived from insights into the cracking of thin layers and is mainly based on the elastic strain energy available to drive crack opening in a critical temperature interval. The underlying thermo-mechanical process simulations are implemented in a custom computational framework designed to efficiently model powder bed fusion. The model predictions are validated against experimentally measured crack densities in CMSX-4 processed by electron beam powder bed fusion. The proposed model allows for rationalizing the dependence of cracking susceptibility on the thermal history, which is controlled by scan speed and beam power. Finally, the model is applied to develop a crack mitigation strategy by reducing the built-up strain energy density. This is achieved by heating the melting area to a high temperature before melting, thereby reducing the temperature gradient.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Additive manufacturing; Electron beam melting; Hot cracking; Ni-base superalloys; Thermo-mechanical modeling